Exercise preference in stroke survivors: a concept analysis - Dai, Yuting; Shi, Huiling; Ji, Kangling; Han, Yuxin; De Ala, Minerva; Wang, Qing (Frontiers in Neurology, 2024)
Background: The exercise preference in stroke survivors is related to the adherence to long-term rehabilitation and functional recovery. Although explored recently, the term still lacks a clear definition. Objective: To conceptualize exercise preference in stroke survivors. Methods: The Walker and Avant method was adopted in this concept analysis as a framework. Data from 34 publications were collected using seven databases (PubMed, Web of Science, Embase, CINAHL, CNKI, Wanfang Data and CBM) and applied in the analysis. The search period was from database inception to April 30,2023. Results: Exercise preference in stroke was defined according to four attributes: priority of choice, behavioral tendency, affective priming, and patience in adherence. Common antecedents of the concept of exercise preference in stroke survivors were classified into patient-related, therapy-related and environmental-related categories and the consequences were classified into the three categories of patient-related, rehabilitation provider-related, and rehabilitation service system-related. Conclusion: Exercise preference in stroke survivors refers to the patient’s choice, tendency, affective and attitude of engagement in the recommended rehabilitation regimen. It is beneficial for understanding the essential attributes of exercise preference in stroke survivors by clarifying the concept. In addition, it will facilitate the development of instruments for assessing the exercise preference in stroke survivors and the construction of theory-based intervention programs that can improve adherence to exercise rehabilitation.